Total Knee Replacement –Histopathological Patterns - Ammara Ijaz (Journal of Rawalpindi Medical College, 2017)
To determine the frequency of different degenerative joint diseases and their morphological changes seen in total knee replacement specimens. Methods: In this descriptive study total knee replacement specimen of 130 patients undergoing bilateral or unilateral knee arthroplasty were included. All specimens were received in 10% formaline fixative and routinely processed and stained with haematoxylin and eosin (H&E).These were examined microscopically and various histological patterns were evaluated. Results: A total of 130 cases of total knee replacement specimen were evaluated. The age range was 43-81 years. The most frequent finding was osteoarthritis which was in 121 cases, 8 cases were of rheumatoid arthritis and one of gouty arthritis. Conclusion: Osteoarthritis with female predominance is the most common pathological finding amongst various patterns.